Qualidade da carne suína: efeito da inclusão de óleo de linhaça e bagaço de uva na dieta - Trombetta, Francielle (2019)
The inclusion of natural products with antioxidant action in the animal feed, as well as the use of different lipid sources, especially n-3 polyunsaturated fatty acids (n-3 PUFA), are nutritional strategies that have been studied to incorporate these compounds into the effect. The presence of n-3 in meat is intended to promote the physiological-functional appeal of these fatty acids, while the presence of natural antioxidants can result in positive effects on the shelf life of the product, as well as promoting a healthier connotation. Thus, the objective of this study was to evaluate the effect of inclusion in the diet of linseed oil (n-3 fatty acid source) and grape pomace (antioxidant source) on weight gain, carcass characteristics, shelf life and shelf life of pork meat. A total of 44 animals from F1 (50% Large White x 50% Landrace) breeders with an Embrapa MS115 clown with an average body weight of 48.6 kg were randomly assigned to four treatments with 11 animals per treatment (4 machos and 4 Females), were raised to slaughter weight (120kg), with free food and water supply and weekly body weight control. The treatments consisted of the following diets: soybean meal control (CONT); with the addition of 3% linseed oil (3% OL); with 3% linseed oil and 3.5% dry grape pomace silage (3.5% SBU); and diet with 3% linseed oil and 7.0% of grape pomace silage on dry basis (7% SBU). During the slaughter procedure, the weight of the hot and cold carcass was recorded, the pH was measured 45 minutes and 24 hours after death in the Longissimus thoracis and lumborum (LTL) muscle, between the 11th and 12th ribs of the left half carcasses. Visual assessments of muscle color and marbling, loin eye area, dorsal fat thickness were measured at the level of the first rib, last rib, last lumbar vertebra and halfcarcass cross-section between the 11th and 12th ribs using a caliper and drip loss. The LTL muscle was analyzed 24 hours after slaughter by chemical composition, fatty acid profile, cooking loss, texture profile, water activity, pH, coloration, oxidative and protein stability, as well as the acceptability of the products throughout its slaughter. Shelf life for 12 days of vacuum packed storage under refrigeration at 4 ° C, as well as sensory analysis. The inclusion of OL and SBU in the pig diet did not affect weight gain, generated a final product with higher nutritional value (increased proportion of polyunsaturated fatty acids / saturated fatty acids (AGPI / AGS) and reduction of n-ratio). 6 / n-3, without affecting the sensory parameters. As for the shelf-life of pork during storage under commercial refrigeration conditions (4ºC), the inclusion of SBU at 7% resulted in meat with similar lipid stability to the control diet. Therefore, the addition of OL and SBU to the pig diet can be adopted as a strategy to improve the fatty acid profile of meat and meat products, with oxidative stability similar to meat of pigs fed diets without lipid source. At the same time, the use of grape pomace in the pig finishing diet proved to be an alternative for recycling this residue that presents high potential for environmental contamination.